Doctors beyond the wall of the hospital: Reflections of Community Based Actions of University Fistula Center, BSMMU - Chowdhury, Shuily; Chowdhury, Saleha Begum; Alam, Farhana (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To describe the community-based interventions of University Fistula Center (UFC), Bangabandhu Sheikh Mujib Medical University (BSMMU) for prevention and care of female genital fistula. Methods: Since January 2017, UFC implemented a range of field-based activities with local partners. This has been systematically documented using an aggregated DHIS2 database introduced by the Fistula Care Plus Project (FC+) as well as process narratives. Results: During this period, UFC implemented 04 community based fistula diagnosis events. Through CFDES, we provided services to 180 women, confirmed diagnosis of fistula in 25 cases, and provided treatment, referral for repairing, counseling and rehabilitation services for them as appropriate. We provided orientation to 238 community level providers on fistula. Through the “School Girls for Fistula Free Bangladesh” we have reached 900 girls with fistula sessions and a roadmap for fistula-free communities led by adolescent girls. Conclusions: Beyond the wall of the hospital, doctors and nurses mobilized by the UFC made a significant contribution at community level to end fistula in Bangladesh by 2030. Keywords: community, doctors beyond the wall, university fistula center